Simple Ciprofloxacin Resistance Test and Determination of Minimal Inhibitory Concentration within 2 h Using Raman Spectroscopy - Kirchhoff, Johanna; Glaser, Uwe; Bohnert, Juergen A.; Pletz, Mathias W.; Popp, Jürgen; Neugebauer, Ute (Analytical Chemistry, 2018)
Resistant bacteria are spreading worldwide, which makes fast antibiotic susceptibility testing and determination of the minimal inhibitory concentration (MIC) urgently necessary to select appropriate antibiotic therapy in time and, by this, improve patient's outcome and, at the same time, avoid inappropriate treatment as well as the unnecessary use of broad spectrum antibiotics that would foster further spread of resistant bacteria. Here, a simple and fast Raman spectroscopy-based procedure is introduced to identify antimicrobial susceptibilities and determine the MIC within only 2 h total analysis, marking a huge time savings compared to established phenotypic methods nowadays used in diagnostics. Sample preparation is fast and easy as well as comparable to currently established tests. The use of a dielectrophoresis chip allows automated collection of the bacteria in a micron-sized region for high-quality Raman measurement directly from bacterial suspensions. The new Raman spectroscopic MIC test was validated with 13 clinical E. coli isolates that show a broad range of ciprofloxacin resistance levels and were collected from patients with blood-stream infection. Micro-Raman spectroscopy was able to detect ciprofloxacin-induced changes in E. coli after only 90 min interaction time. Principal component analysis as well as a simple computed ratio of the Raman marker bands at 1458 and 1485 cm-1 show a clear concentration-dependent effect. The MIC values determined with the new Raman method are in good agreement with MICs obtained by reference methods (broth microdilution, Vitek-2, E-test) and can be used to provide a classification as sensitive, intermediate, or resistant using the clinical breakpoints provided by EUCAST.
CRIS-Team Scopus Importer:2023-04-20